Study of red-emitting LaAsO4:Eu3+ phosphor for color rendering index improvement of WLEDs with dual-layer remote phosphor geometry - My Hanh Nguyen Thi; Nguyen Thi Phuong Loan; Nguyen Doan Quoc Anh (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
The remote phosphor structure is often disadvantageous in color quality but in terms of optics it is more convenient when compared to other phosphor structures such as conformal or in-cup ones. From this disadvantage, there are many studies to improve its chromatic output. In this research paper, we propose a dual-layer remote phosphor geometry for the improvement of white light-emitting diodes (WLEDs) in two parameters: color rendering index (CRI) and color quality scale (CQS). The 7700 K WLEDs are used in this study. The idea of the study is to place a red phosphor layer LaAsO4:Eu3+ on the yellow phosphor YAG: Ce3+, and then find the concentration of LaAsO4:Eu3+ in an appropriate way to achieve the highest color quality. The results showed that LaAsO4:Eu3+ bring great benefits for enhancing CRI and CQS. In particular, the greater the concentration of LaAsO4:Eu3+, the greater the CRI and CQS because the portion of red lights in WLEDs increases. However, the decrease in lumen output occurs when the concentration of LaAsO4:Eu3+ increases excessively. This is proved thanks to Mie-scattering theory and Beer-Lambert law. The results of important articles in WLEDs fabrication have greatly contributed to a higher white light quality.